2018
DOI: 10.12659/aot.906372
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Immunosuppression on Target Blood Immune Cells Within 1 Year After Lung Transplantation: Influence of Age on T Lymphocytes

Abstract: BackgroundLymphocytes are targeted by immunosuppressive therapy in solid organ transplantation and they influence allograft outcome.Material/MethodsPeripheral blood lymphocyte subsets (PBLS) determined by flow cytometry during the first year post-transplant from patients who underwent a first lung transplantation in a French University Hospital between December 2011 and July 2013 were retrospectively analyzed according to recipient characteristics and allograft outcome.ResultsFifty-seven recipients were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In vaccinated patients who underwent lung transplantation, VZV IgG concentrations declined starting at 1 month after transplantation, but they were still higher than at baseline levels during the follow-up period, in contrast to the relatively stable level in unvaccinated patients who underwent transplantation. 29 Lowest VZV SFCs levels were seen at 1 month after transplantation in both groups, and this could be due to the strong effects of short-term immunosuppressants, which target T lymphocytes. VZV-specific CMI returned to a high level after a median time of 7.3 months after transplantation.…”
Section: Discussionmentioning
confidence: 91%
“…In vaccinated patients who underwent lung transplantation, VZV IgG concentrations declined starting at 1 month after transplantation, but they were still higher than at baseline levels during the follow-up period, in contrast to the relatively stable level in unvaccinated patients who underwent transplantation. 29 Lowest VZV SFCs levels were seen at 1 month after transplantation in both groups, and this could be due to the strong effects of short-term immunosuppressants, which target T lymphocytes. VZV-specific CMI returned to a high level after a median time of 7.3 months after transplantation.…”
Section: Discussionmentioning
confidence: 91%
“…It is known that mitosis is age-related process as well as other components of immune system. [33][34][35] It was posited that a combination of adjuvantation systems may provide enhanced immune activation but has typically been developed without regard to the age of the target population and distinct combinations of TLRAs and C-type lectin receptor agonists may enhance Th1 responses of newborn DCs. Neutrophils, monocyte/macrophages and dendritic cells, which first recognize and respond to infection, show age-related impairment of many functions relevant to anti-viral responses.…”
Section: Discussionmentioning
confidence: 99%
“…There was a positive correlation between the number of lymphocytes and the immunity of the body (Dar et al, 2018, Argente et al, 2019. With the aging of body, The amount of T cells declines and the immune decline (Chason et al, 2018).The number and subpopulations of T cells in peripheral blood also change which results in the decrease of CD 3 + 0CD 4 + and CD 8 + T cells (Coiffard et al, 2018, Ilienko et al, 2017, Sanderson and Simon, 2017. Our study also found peripheral CD 3 + 0CD 4 + and CD 8 + T cells significantly decreased in the aging rats compared to the young control rats.…”
Section: G0/g1 + S + G2mmentioning
confidence: 99%